Nanoethosomal transdermal delivery of vardenafil for treatment of erectile dysfunction: optimization, characterization, and in vivo evaluation - Fahmy UA (Dove Medical Press, 2015)
Usama A Fahmy Department of Pharmaceutics & Industrial Pharmacy, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Saudi Arabia Abstract: Vesicular drug delivery systems have recently gained attention as a way of improving dosing accuracy for drugs with poor transdermal permeation. The current study focuses on utilization of the natural biocompatible vesicles to formulate vardenafil nanoethosomes (VRD-NE), for the enhancement of their transdermal permeation and bioavailability. Fifteen formulations were prepared by thin-layer evaporation technique according to Box–Behnken design to optimize formulation variables. The effects of lipid composition, sonication time, and ethanol concentration on particle size and encapsulation efficiency were studied. The diffusion of vardenafil (VRD) from the prepared nanoethosomes specified by the design was carried out using automated Franz diffusion cell apparatus. The optimized formula was investigated for in vivo pharmacokinetic parameters compared with oral VRD suspension. Confocal laser scanning microscopy images were used to confirm enhanced diffusion release of VRD in rat skin. The results showed that the optimized formula produced nanoethosomes with an average size of 128 nm and an entrapment efficiency of 76.23%. VRD-NE provided a significant improvement in permeation with an enhancement ratio of 3.05-fold for a film made with optimally formulated VRD-NE compared with a film made with VRD powder. The transdermal bioavailability of VRD from the nanoethosome film was approximately twofold higher than the oral bioavailability from an aqueous suspension. VRD-NE thus provide a promising transdermal drug delivery system. As a result, management of impotence for a longer duration could be achieved with a reduced dosage rate that improves patient tolerability and compliance for the treatment of erectile dysfunction.Keywords: Box–Behnken design, impotence, vesicles, nanoparticles